Reforming Scottish Criminal Procedure: In Search of Process Values - Ferguson, Pamela R. (Bergen Journal of Criminal Law & Criminal Justice, 2017)
Recent proposals to reform Scottish criminal procedure are motivated by considerations of efficiency and accurate fact-finding, and there is little attempt to offer a normative account. This paper describes these proposals and contends that their emphasis on finding ‘the truth’ is misplaced on two distinct bases: (1) it equates erroneous acquittals to wrongful convictions, thus fails to uphold a fundamental tenet of criminal procedure, namely the particular importance of protecting the innocent against wrongful conviction; and (2) it fails to recognise the importance of non-instrumental process values which are at the heart of the adversarial criminal trial. The paper suggests that it is only by adhering to these process values that the state maintains – and demonstrates that it maintains – its moral authority to condemn and punish offenders. Key notes: Return Directive, entry ban, illegal migrant, criminal law sanctions, crimmigration, expulsion.